Bactericidal mechanisms of Ag2O/TNBs under both dark and light conditions - Jin, Yinjia; Dai, Zhaoyi; Liu, Fei; Kim, Hyunjung; Meiping Tong; Yanglong Hou (Water Research, 2013)
Ag2O/TNBs were fabricated by depositing Ag2O nanoparticles on the surface of TiO2 nanobelts (TNBs). The disinfection activities of Ag2O/TNBs on two representative bacterial types: Gram-negative Escherichia coli ATCC15597 and Gram-positive Bacillus subtilis, were examined under both dark and visible light conditions. Ag2O/TNBs exhibited stronger bactericidal activities than Ag2O nanoparticles and TNBs under both dark and light conditions. For both cell types, disinfection effects of Ag2O/TNBs were greater under light conditions relative to those under dark conditions. The bactericidal mechanisms of Ag2O/TNBs under both dark and light conditions were explored. Ag+ ions released from Ag2O/TNBs did not contribute to the bactericidal activity of Ag2O/TNBs under dark conditions, whereas the released Ag+ ions showed bactericidal activity under visible light irradiation conditions. Active species (H2O2, O-center dot(2)-, and e(-)) generated by Ag2O/TNBs played important roles in the disinfection processes under both dark and visible light irradiation conditions. Without the presence of active species, the direct contact of Ag2O/TNBs with bacterial cells had no bactericidal effect. (C) 2013 Elsevier Ltd. All rights reserved.